Condannati al paradiso terrestre. Belle Fenoglio tra Hopkins e Marziale - Giancarlo Alfano (Parole Rubate, 2023)
This essay highlights how Fenoglio contrasts, on the one hand, the world of the resistance movement and, on the other, the world at the end of World War II. The first dimension is described as an “absolute” world, namely something that has taken place; the second dimension, instead, is the world of “repetition”, that is to say something that keeps repeating. This opposition is quite clear both in Fenoglio’s works and in Fenoglio’s literary evolution. Indeed, the writer represents daily life as a form of repetition. This contrast finds also a parallel in the two poets Fenoglio looks at in the post-war years: Hopkins, the partisan’s sublime poet, versus Martial, epigrammatic poet of everyday trifles.